Biopotency of indian privet, Vitex negundo Linn.(Verbenaceae) against spodoptera litura fab.(Lepidoptera: Noctuidae) and Henosepilachna vigintioctopunctata Fab. Ccoleoptera:Coccinellidae) - Deepthy K B. (Department of Agricultural Entomology, College of Horticulture, 2009)
The present investigations on “Biopotency of Indian privet, Vitex negundo Linn. (Verbenaceae) against Spodoptera litura Fab. (Lepidoptera: Noctuidae) and Henosepilachna vigintioctopunctata (Coleoptera: Noctuidae) were carried out in the Department of Agricultural Entomology, College of Horticulture, Vellanikkara during 2005-2008. The objectives of this study were to screen the different parts (leaf, shoot and flower) of V. negundo for its biological efficiency with different solvent extracts against S. litura and H. vigintioctopunctata and to test the V. negundo extracts for their biological responses as with ovipositional deterrency, ovicidal action, antifeedancy, morphogenic effects and reproductive inhibition against the test insects. Experiments were also conducted to assess the potency of V. negundo extracts in combination with different entomopathogens. Screening experiments revealed that among the different parts viz., leaves, shoots and flowers of V. negundo, leaves showed significant bio response against S. litura and H. vigintioctopunctata. Methanol and hexane extract of leaves of V. negundo at six per cent resulted in maximum mortality of S. litura and H. vigintioctopunctata. V. negundo extracts with methanol (6%) indicated significant ovipositional deterrency with 94.02 and 100 per cent reduction in egg laying of S. litura and H. vigintioctopunctata respectively. Methanol extract (6%) proved as an efficient ovicidal agent against S. litura. Against H. vigintioctopunctata acetone aqueous extracts showed pronounced ovicidal action at lower concentration of four per cent resulting in cent percent reduction in hatching. Studies on growth and developmental effects of V. negundo extracts revealed that methanol and acetone extracts resulted in maximum reduction in pupal weight and pupation of S. litura. Delay in moulting of S. litura was observed in different treatments with V. negundo. S. litura reared in treated castor leaves and semi synthetic diet recorded maximum larval duration (19 and 26 days respectively) with acetone (6%) while water extract resulted in greater duration of 17.67 days in banana fed larvae. V. negundo cause no antifeedant action against S. litura and H. vigintioctopunctata. Food consumption and utilization studies on S. litura and H. vigintioctopunctata revealed that V. negundo extracts caused a drastic decline in growth parameters like, Efficiency of Conversion of Ingested Food (ECI) and Efficiency of Conversion of Digested Food (ECD), larval growth and Relative Growth Rate (RGR) thus indicating the inhibitory action of V. negundo on the growth of test insects. All the solvent extracts (except aqueous extract) reduced ECI and ECD against both S. litura and H. vigintioctopunctata proving the potency of V. negundo as an efficient growth inhibitor. Acetone extract (6%) resulted in maximum reduction in RCR of S. litura and H. vigintioctopunctata. Hexane, acetone and methanol extracts caused highest growth inhibition in H. vigintioctopunctata. Correlation studies revealed that there is a highly significant positive correlation of ECI and ECD with RGR both in S. litura and H. vigintioctopunctata. Solvent extracts of V. negundo were found to induce pupal and adult malformations in S. litura and H. vigintioctopunctata. Hexane and methanol extracts caused highest pupal and adult malformations in S. litura larvae. All the solvent extracts (6%) caused significant reduction in longevity and fecundity of both S. litura and H. vigintioctopunctata. Methanol extract was proved to be the most toxic (least LD50 value) against S. litura and against H. vigintioctopunctata, hexane extract showed maximum toxicity. Compatibility studies revealed that methanol extract inhibited growth of both Metarhizium anisopliae and Beauveria bassiana. Combination treatment of methanol extract with M. anisopliae resulted in reduction in mortality of S. litura leading to antagonistic interaction. Combination studies conducted with Bacillus thuringiensis and Nuclear Polyhedrosis Virus (NPV) resulted in enhanced mortality and reduction in Median Lethal Time (LT50). The results of the present study thus indicate the multiple modes of action of V. negundo against insect pests and hence there is good scope of its utilization as an efficient component in Integrated Pest Management (IPM) programmes against S. litura and H. vigintioctopunctata.